2001
DOI: 10.1179/irs.2001.28.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Cold bonded ore–coal composite pellets for sponge ironmaking Part 2 Plant trials in rotary kiln

Abstract: Cold bonded ore-coal composite pellets developed on a laboratory scale (Part 1 of this two part paper) were tested in a rotary kiln sponge iron plant. This plant had a 12 m length refractory lined rotary kiln of 8 t/day iron ore throughput capacity. Kiln operation was optimised to achieve more than 90% metallisation of sponge iron using ore-coal composite pellets. The kiln productivity increased and energy consumption decreased, compared with levels obtained when sized lump ore was used as iron oxide feed mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…In the literature, there are mainly studies on the production of self-reducing or composite pellets with organic substances. [6][7][8][9][10][11][12][13][14][15] However, the addition of carbon usually lowers the strength of agglomerates. Therefore, briquettes normally contain less than 10 wt% carbon.…”
Section: Briquetting With a Bindermentioning
confidence: 99%
“…In the literature, there are mainly studies on the production of self-reducing or composite pellets with organic substances. [6][7][8][9][10][11][12][13][14][15] However, the addition of carbon usually lowers the strength of agglomerates. Therefore, briquettes normally contain less than 10 wt% carbon.…”
Section: Briquetting With a Bindermentioning
confidence: 99%
“…In the 1990s, an attempt was made at SAIL R&D center, Ranchi, India, to use composite pellets as the feed material in a pilot-scale rotary kiln of 8.0 tons per day [85]. The curing of the green pellets using organic binder was done by keeping them in open-atmosphere for 4-7 days to attain dry compression strength of 350-400 N/pellet, and then those were used for reduction.…”
Section: Industrial Use Of Iron Ore-coal Composite Pelletmentioning
confidence: 99%
“…Many investigators such as Agrawal et al (2000Agrawal et al ( , 2001, Rani Devi and Mazumder (2007), and Misra and Ipicol (2006) considered sponge iron manufacturing process and suggested improvement in it. It is found that during operation in coal-based sponge iron plant a tremendous amount of heat is generated.…”
Section: Introductionmentioning
confidence: 98%